2013
DOI: 10.1038/ejhg.2013.93
|View full text |Cite
|
Sign up to set email alerts
|

Rare copy number variation in cerebral palsy

Abstract: Recent studies have established the role of rare copy number variants (CNVs) in several neurological disorders but the contribution of rare CNVs to cerebral palsy (CP) is not known. Fifty Caucasian families having children with CP were studied using two microarray designs. Potentially pathogenic, rare (o1% population frequency) CNVs were identified, and their frequency determined, by comparing the CNVs found in cases with 8329 adult controls with no known neurological disorders. Ten of the 50 cases (20%) had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 47 publications
1
51
0
4
Order By: Relevance
“…Currently the combination of 14% of cases with individually likely pathogenic point mutations found by WES and 20-31% with CNVs of interest gives a potential genetic contribution to causation in up to 34-45% of cerebral palsy cases. This new study also reinforces the conclusions of previous CNV56 and WES 12 studies suggesting considerable genetic heterogeneity of cerebral palsy.Sophisticated functional studies are required to validate genetic findings. Plethora of approaches using either in silico tools, animal models like zebrafish, fruit fly or mice or stem cells (i.e.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Currently the combination of 14% of cases with individually likely pathogenic point mutations found by WES and 20-31% with CNVs of interest gives a potential genetic contribution to causation in up to 34-45% of cerebral palsy cases. This new study also reinforces the conclusions of previous CNV56 and WES 12 studies suggesting considerable genetic heterogeneity of cerebral palsy.Sophisticated functional studies are required to validate genetic findings. Plethora of approaches using either in silico tools, animal models like zebrafish, fruit fly or mice or stem cells (i.e.…”
supporting
confidence: 89%
“…Contribution of the dosage imbalances or copy number variants (CNVs) is yet to be fully assessed. Ten out of 50 singleton cerebral palsy cases had potentially relevant CNVs in our pilot study 56 . However, all these CNVs were inherited from a healthy parent suggesting another genetic or environmental contributing factor.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cerebral palsy (CP) has been occasionally described in patients with microdeletion [Peredo et al, 2013;Zahanova et al, 2012] and microduplication syndromes [Degerliyurt et al, 2012]. A recent study of 50 cases with CP revealed the presence of rare copy number variants (CNVs) of potential relevance to CP [McMichael et al, 2014]. Accordingly, rare CNVs with probable causative roles have been identified in up to 19% of patients with Lennox-Gastaut syndrome, a severe epileptic encephalopathy [Lund et al, 2013]; thus, a-CGH has been suggested as the first-line genetic analysis for West syndrome [Hansen et al, 2012].…”
Section: Introductionmentioning
confidence: 96%
“…[20][21][22] CNV analysis may be diagnostically and prognostically valuable in clinical settings, and CNV studies of CP cohorts have already been instructive by implicating genes relevant to CP neurobiology within the genomic interval that has been duplicated or deleted. [20][21][22] CNV analysis may be diagnostically and prognostically valuable in clinical settings, and CNV studies of CP cohorts have already been instructive by implicating genes relevant to CP neurobiology within the genomic interval that has been duplicated or deleted.…”
mentioning
confidence: 99%